Fungicide ingestion reduces net energy gain and microbiome diversity of the solitary mason bee - Mitzy F. Porras; Juan Antonio Raygoza Garay; Malachi Brought; Tomas López–Londoño; Alexander Chautá; Makaylee Crone; Edwin G. Rajotte; Ngoc Phan; Neelendra K. Joshi; Kari Peter; David Biddinger (Scientific Reports, 2024)
Abstract Fungicides are frequently used during tree fruit bloom and can threaten insect pollinators. However, little is known about how non-honey bee pollinators such as the solitary bee, Osmia cornifrons, respond to contact and systemic fungicides commonly used in apple production during bloom. This knowledge gap limits regulatory decisions that determine safe concentrations and timing for fungicide spraying. We evaluated the effects of two contact fungicides (captan and mancozeb) and four translaminar/plant systemic fungicides (cyprodinil, myclobutanil, penthiopyrad, and trifloxystrobin) on larval weight gain, survival, sex ratio, and bacterial diversity. This assessment was carried out using chronic oral ingestion bioassays where pollen provisions were treated with three doses based on the currently recommended field use dose (1X), half dose (0.5X), and low dose (0.1X). Mancozeb and penthiopyrad significantly reduced larval weight and survival at all doses. We then sequenced the 16S gene to characterize the larvae bacteriome of mancozeb, the fungicide that caused the highest mortality. We found that larvae fed on mancozeb-treated pollen carried significantly lower bacterial diversity and abundance. Our laboratory results suggest that some of these fungicides can be particularly harmful to the health of O. cornifrons when sprayed during bloom. This information is relevant for future management decisions about the sustainable use of fruit tree crop protection products and informing regulatory processes that aim to protect pollinators.